Democratization and Development
XII, 196 p.
Keywords: Exploring the political economy of development and democracy in the Middle East, this book provides new insight into the effects of external initiatives for the support of good governance in Arab states, the impact of transnational Islamist networks on democratization in the Middle East, and the role of new satellite broadcasting in the Arab world.